2022
DOI: 10.1002/aur.2867
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of associations between primarily non‐autistic people's characteristics and attitudes toward autistic people

Abstract: This systematic review includes a narrative synthesis and meta‐analysis of research on the associations between primarily non‐autistic people's characteristics and their attitudes toward autistic people. Of 47 studies included in the narrative synthesis, White undergraduate students were surveyed most frequently. Demographic characteristics were the factors most frequently tested for associations with attitudes, followed by contact‐related factors (i.e., quantity and quality), knowledge about autism, trait and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…For instance, a recent review of research on the associations between individual characteristics and attitudes toward autistic people revealed that women and those with more autism knowledge and more frequent and high-quality contact with autistic people tend to have less stigma toward autistic people than their counterparts (S. Y. Kim et al, 2023). This suggests that men may need more training than women, and increasing knowledge and providing opportunities for contact with autistic people may reduce autism stigma.…”
Section: Autism Stigma and Anti-stigma Interventionsmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, a recent review of research on the associations between individual characteristics and attitudes toward autistic people revealed that women and those with more autism knowledge and more frequent and high-quality contact with autistic people tend to have less stigma toward autistic people than their counterparts (S. Y. Kim et al, 2023). This suggests that men may need more training than women, and increasing knowledge and providing opportunities for contact with autistic people may reduce autism stigma.…”
Section: Autism Stigma and Anti-stigma Interventionsmentioning
confidence: 99%
“…While coding for bias due to confounding, we considered participants' gender, knowledge about autism, and quality and quantity of previous contact as potentially confounding factors based on evidence from a recent meta-analytic review, which found these variables were correlated with raters' stigma toward autistic people (S. Y. Kim et al, 2023). We considered the bias due to confounding as high-risk if the analysis did not statistically account for these factors.…”
Section: Coding Proceduresmentioning
confidence: 99%
See 3 more Smart Citations